6-Methoxyflavone and Donepezil Behavioral Plus Neurochemical Correlates in Reversing Chronic Ethanol and Withdrawal Induced Cognitive Impairment - Arif M; Rauf K; Rehman NU; Tokhi A; Ikram M; Sewell RD (Dove Medical Press, 2022)
Mehreen Arif,1 Khalid Rauf,1 Naeem Ur Rehman,1 Ahmed Tokhi,1 Muhammad Ikram,1 Robert D Sewell2 1Department of Pharmacy, COMSATS University Islamabad, Abbottabad Campus, Abbottabad, Khyber Pakhtoonkhwa, 22060, Pakistan; 2Cardiff School of Pharmacy and Pharmaceutical Sciences, Cardiff University, Cardiff, CF10 3NB, UKCorrespondence: Khalid Rauf, Department of Pharmacy, COMSATS University Islamabad, Abbottabad Campus, Abbottabad, Khyber Pakhtoonkhwa, 22060, Pakistan, Tel +923459824468, Email khalidrauf@cuiatd.edu.pkPurpose: Chronic ethanol exposure causes neurotoxicity and long-term learning and memory impairment along with hippocampal and frontal cortical dysfunction. Flavonoids possess antioxidant and anti-inflammatory properties believed to be contributory factors in reversing cognitive decline. 6-Methoxyflavone (6-MOF), a flavonoid occurring naturally in medicinal plants, has been reported to instigate neuroprotection by reversing cisplatin-induced hyperalgesia and allodynia. Consequently, this study was designed to investigate 6-MOF activity in models of chronic ethanol-induced cognitive impairment along with neurochemical correlates.Methods: Mice were given ethanol orally (2.0 g/kg daily) for 24 days plus either saline, 6-MOF (25- 75mg/kg) or donepezil (4mg/kg) and then ethanol was withdrawn for the next 6 days. Animals were subsequently assessed for their cognitive performance in several models on days 1, 12, and 24, during abstinence (Day-26) and on the 7th day of the washout period. Following behavioral assessment, post-mortem dopamine, noradrenaline and vitamin C concentrations were quantified in the frontal cortex, hippocampus and striatum, using HPLC with UV detection.Results: Chronic ethanol treatment suppressed locomotor activity and impaired cognitive tasks, which included novel object recognition, performance in the Morris water maze as well as the Y-maze, socialization and nest-building behavior throughout the protocol and during withdrawal. These behavioral deficits were at least partially restored by the co-administration of 6-MOF or donepezil with ethanol as were ethanol-induced deficits in frontal cortical and hippocampal dopamine plus noradrenaline, together with striatal dopamine. 6-MOF co-administration with ethanol also modestly restored striatal vitamin C levels.Conclusion: It is postulated that, apart from donepezil, 6-MOF may be useful not only in the treatment of ethanol withdrawal severity but also in the management of chronic ethanol withdrawal induced cognitive impairment.Keywords: ethanol cognition, 6-methoxyflavone, dopamine, noradrenaline, hippocampus, frontal cortex